Performance of a triple-GEM demonstrator in pp collisions at the CMS detector. (12th November 2021) - Abbas, M.; Abbrescia, M.; Abdalla, H.; Abdelalim, A.; AbuZeid, S.; Agapitos, A.; Ahmad, A.; Ahmed, A.; Ahmed, W.; Aimè, C.; Aruta, C.; Asghar, I.; et al.
Abstract: After the Phase-2 high-luminosity upgrade to the Large Hadron Collider (LHC), the collision rate and therefore the background rate will significantly increase, particularly in the high η region. To improve both the tracking and triggering of muons, the Compact Muon Solenoid (CMS) Collaboration plans to install triple-layer Gas Electron Multiplier (GEM) detectors in the CMS muon endcaps. Demonstrator GEM detectors were installed in CMS during 2017 to gain operational experience and perform a preliminary investigation of detector performance. We present the results of triple-GEM detector performance studies performed in situ during normal CMS and LHC operations in 2018. The distribution of cluster size and the efficiency to reconstruct high pT muons in proton-proton collisions are presented as well as the measurement of the environmental background rate to produce hits in the GEM detector.